Galileo Galilei: A Pioneer of Modern Science - Zachou, Stella; Tzorva, Catherine (Open Schools Journal for Open Science, 2025)
Galileo Galilei revolutionized scientific thought with his empirical approach to physics and astronomy. His support of heliocentrism, despite fierce opposition from the Church, marked a turning point in the history of science. This paper explores Galileo’s contributions, the socio-religious tensions of his time, and his enduring legacy.